(untitled) (Research, Society and Development, 2022)
Objective: To investigate the presence of dyslipidemia and nutritional status in a group of patients, aged from zero to twelve years, living in the city of Goiânia. Methodology: Analytical case series study, in which 130 electronic records of patients aged 0-12 years living in Goiânia were analyzed. Participants were divided into four groups of different age groups: group 1 are children aged zero to three years, group 2 from four to six, group 3 from seven to nine and group 4 from ten to twelve years old. The data collected were: gender, age, weight, height and altered laboratory tests. The Z-Score was calculated in Cookie® professional softwear and follows the recommendations of SISVAN/DATASUS (Food and Nutritional Surveillance) which are based on WHO criteria. And dyslipidemia was classified according to the elevation of the lipid profile. The data obtained were arranged in spreadsheets in Microsoft Excel® (Office 2007 version) and descriptive statistics were used to process the results. Results: In group 1, 40 medical records were analyzed and it was observed that 40% of the children had dyslipidemia and 5% were obese, the association of dyslipidemia and obesity was 0%. Of the 30 medical records analyzed in group 2, 20% had dyslipidemia and 17% were obese, 6.7% were obese and dyslipemic. In group 3, 30 children were analyzed, 40% had dyslipidemia and 23% obesity, 6.7% were obese and dyslipidemic. In group 4, after evaluating 30 medical records, it was observed that 30% of the adolescents had dyslipidemia and 60% were obese, the association between dyslipidemic and obese was 13.3%. Conclusion: A significant number of children and adolescents living in Goiânia were found to have dyslipidemia and obesity, but the fact that children were obese is not necessarily associated with dyslipidemia. Such data are important for the elaboration of public health policies that can help in SISVAN/DATASUS statistics. In this way, encourage the population of Goiás and other communities to take care of their food. The best way to prevent and treat these diseases in childhood is diet therapy and regularization of physical activity.